2006
DOI: 10.1111/j.1540-8191.2006.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor Provides a Novel Local Angiogenic Therapy for Ischemic Cardiomyopathy

Abstract: Intramyocardial delivery of PlGF following a large myocardial infarction enhanced border zone angiogenesis, attenuated adverse ventricular remodeling, and preserved cardiac function. This therapy may be useful as an adjunct or alternative to standard revascularization techniques in patients with ischemic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…27 Kolakowski and colleagues were able to demonstrate the beneficial effects of PlGF on the infarcted heart after direct myocardial injection. 4 In the present study, similar results were obtained when comparing groups I and II in regards to LVEF, scar area, and angiogenesis analysis. Protein delivery was optimized by using the same PlGF dosage as in previous studies but with better results due to the use of nanoparticles as the drug delivery system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…27 Kolakowski and colleagues were able to demonstrate the beneficial effects of PlGF on the infarcted heart after direct myocardial injection. 4 In the present study, similar results were obtained when comparing groups I and II in regards to LVEF, scar area, and angiogenesis analysis. Protein delivery was optimized by using the same PlGF dosage as in previous studies but with better results due to the use of nanoparticles as the drug delivery system.…”
Section: Discussionsupporting
confidence: 86%
“…One of these factors is placental growth factor (PlGF). 4 PlGF is a 50 kDa homodimeric glycoprotein sharing 53% sequence homology at the amino acid level with vascular endothelial growth factor (VEGF). PlGF is able to bind with high affinity to the fms-like tyrosine kinase (Flt-1) receptor but not to the kinase domain region receptor, thought to be critically involved in mediating VEGF biological action.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, PlGF seems to have beneficial effects in a number of hypoxia-associated conditions. 6,8 PlGF À/À mice showed a more pronounced increase in VEGF protein levels in the distal colon after DSS administration compared with PlGF þ / þ mice, which was preventable by exogeneous administration of PlGF. Interestingly, this boost in VEGF was not able to compensate for the decrease in angiogenesis caused by the absence of PlGF.…”
Section: Discussionmentioning
confidence: 99%
“…PlGF has been shown to have beneficial effects in wound healing and ischemic cardiac disease. 4,7,8 The function of angiogenesis in IBD pathogenesis remains poorly understood because of its opposing effects. On one hand, angiogenesis is a crucial process to supply oxygen and nutrients to promote healing of the damaged mucosa.…”
mentioning
confidence: 99%
“…Placental growth factor (PlGF), a homolog of VEGF, is reported to stimulate angiogenesis and arteriogenesis [9][10][11] with an efficacy at least comparable to that of VEGF, but without any of the side-effects that normally accompany VEGF therapy, such as edema, hypotension, 12 and hemangioma-genesis. We have recently demonstrated that PlGF is produced rapidly in infarcted myocardial tissue, and that the plasma level of PlGF after MI is positively correlated with the improvement in left ventricular function in patients with AMI.…”
mentioning
confidence: 99%